The development of amine-based extractants for separation of base metals in a sulfate medium - Magwa, Nomampondo Penelope (Rhodes University, Faculty of Science, Department of Chemistry, 2015)
Tridentate benzimidazole-based ligands, bis((1H-benzimidazol-2-yl)methyl)sulfide (BNSN) and bis((1H-benzimidazol-2-yl)methyl)amine (BNNN), along with dinonylnaphthalene sulfonic acid (DNNSA) as a synergist, were investigated as potential selective extractants for Ni2+ from base metals in a solvent extraction system using 2-octanol/Shellsol 2325 (8:2) as diluent and modifier. However, extraction studies show a lack of pH-metric separation of the later 3d metal ions with bis((1-octylbenzimidazol-2-yl)methyl)sulfide (BONSN) and bis((1- decylbenzimidazol-2-yl)methyl)amine (BDNNN) as extractants, but extractions occurred in the low pH range with an opportunity for back extraction. This investigation suggested that tridentate ligands (at least those of the nature investigated here) are not feasible extractants for separation of base metal ions due to their lack of stereochemical "tailor-making."
Keywords: Extraction (Chemistry); Sulfates; Ligands; Benzimidazoles; Infrared spectroscopy; Nuclear magnetic resonance spectroscopy; Metal ions; Metals